Food insecurity, food waste, food behaviours and cooking confidence of UK citizens at the start of the COVID-19 lockdown. Issue 9 (8th September 2021) - Armstrong, Beth; Reynolds, Christian; Martins, Carla Adriano; Frankowska, Angelina; Levy, Renata Bertazzi; Rauber, Fernanda; Osei-Kwasi, Hibbah A.; Vega, Marcelo; Cediel, Gustavo; Schmidt, Ximena; Kluczkovski, Alana; Akparibo, Robert; et al.
Abstract : Purpose: The current pilot study explored food insecurity, food waste, food related behaviours and cooking confidence of UK consumers following the COVID-19 lockdown. Design/methodology/approach: Data were collected from 473 UK-based consumers (63% female) in March 2020. A cross-sectional online survey measured variables including food insecurity prevalence, self-reported food waste, food management behaviours, confidence and frequency of use of a range of cooking methods, type of food eaten (ultra-processed, semi-finished, unprocessed) and packaging type foods are purchased in. Findings: 39% of participants have experienced some food insecurity in the last 12 months. Being younger, having a greater BMI and living in a smaller household were associated with food insecurity. Green leaves, carrots, potatoes and sliced bread are the most wasted of purchased foods. Polenta, green leaves and white rice are the most wasted cooked foods. Food secure participants reported wasting a smaller percentage of purchased and cooked foods compared to food insecure participants. Overall, participants were most confident about boiling, microwaving and stir-frying and least confident with using a pressure cooker or sous vide. Food secure participants were more confident with boiling, stir-frying, grilling and roasting than insecure food participants. Practical implications: This has implications for post lockdown policy, including food policies and guidance for public-facing communications. Originality/value: We identified novel differences in self-report food waste behaviours and cooking confidence between the food secure and insecure consumers and observed demographics associated with food insecurity.